(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2017)
Created for the specifics of military aviation complex multiple psycho-physiological studies of individual biological characteristics of the military cadets of aptitude using a polygraph system military pilot–aircraft–environment were developed. Comprehensive psychological survey of using polygraph allows to evaluate the accuracy of the information on the adequacy of the non-specific physiological responses to verbal answers in the study and solution of problems of the human element in military aviation and prevention of dangerous flight psycho-physiological factors. Psychocorrection of functional disorders of the nervous system revealed using polygraph promotes post stress rehabilitation and maintenance of positive flight motivation of military cadets in the system of psychological security of the flight.